The roman salting factories of La Azohía (Cartagena, Spain). New archaeological perspectives (Salduie, 2026)
Despite producing garum of exceptional quality ac-cording to classical sources, salting factories are scarce in the territory of Carthago Nova (Cartagena). It has been suggested that some ensembles located in coves near the city functioned as industrial districts, such as the bay of Mazarrón. Here, alongside the well-known cetariae of Puerto de Mazarrón, a production complex underestimated by research to date stands out: La Azohía. Within the framework of Project TRAPHIC, this paper compiles and reinterprets the archaeological evidence recorded in this small town from Roman times to the present day, with special at-tention to the modern era. It offers new data on the chronology and functionality of various unpublished fishing and canning facilities in order to reassess their role in the Carthaginensis’ economic system.